The structure of 3'-O-anthraniloyladenosine, an analogue of the 3'-end of aminoacyl-tRNA. - Nawrot, B (1997)
3'-O-Anthraniloyladenosine, an analogue of the 3'- terminal aminoacyladenosine residue in aminoacyl-tRNAs, was prepared by chemical synthesis, and its crystal structure was determined. The sugar pucker of 3'-O-anthraniloyladenosine is 2'-endo resulting in a 3'-axial position of the anthraniloyl residue. The nucleoside is insynconformation, which is stabilized by alternating stacking of adenine and benzoyl residues of the neighboring molecules in the crystal lattice. The conformation of the 5'-hydroxymethylene in 3'-O- anthraniloyladenosine is gauche-gauche. There are two intramolecular and two intermolecular hydrogen bonds and several H-bridges with surrounding water molecules. The predominant structure of 3'-O-anthraniloyladenosine in solution, as determined by NMR spectroscopy, is 2'-endo,gauche-gauche and anti for the sugar ring pucker, the torsion angle around the C4'-C5'bond and the torsion angle around the C1'-N9 bond, respectively. The 2'-endo conformation of the ribose in 2'(3')-O-aminoacyladenosine, which places the adenine and aminoacyl residues in equatorial and axial positions, respectively, could serve as a structural element that is recognized by enzymes that interact with aminoacyl-tRNA or by ribosomes to differentiate between aminoacylated and non-aminoacylated tRNA.